Sustainability factors influencing post-disaster reconstruction projects: Critical review and bibliometric analysis - Ahmed Wajeh Mushtaha; Wesam Salah Alaloul (Sustainable Futures, 2025)
Sustainable post-disaster reconstruction is essential for mitigating vulnerabilities, enhancing resilience, and fostering long-term community recovery. This paper systematically reviews and conducts a bibliometric analysis of 106 articles published between 2014 and 2024, examining sustainability in post-disaster reconstruction projects globally. The review identifies key sustainability factors in reconstruction projects, including green building practices, economic revitalization, and community participation. Publication trends reveal growing international research interest, highlighting diverse geographic contributions yet underscoring critical knowledge gaps and practical challenges. Specifically, limited funding, uneven technology adoption, and insufficient integration of mental health considerations frequently hinder sustainable recovery efforts. The analysis further emphasizes innovative technological tools, including Geographic Information Systems (GIS), Building Information Modelling (BIM), and Artificial Intelligence (AI), which significantly enhance the planning, execution, and coordination of reconstruction initiatives. This paper contributes to bridging existing theoretical and practical gaps by proposing an integrated sustainability framework applicable to diverse disaster contexts, thereby improving policy formulation and implementation effectiveness. By clearly identifying areas for improvement and future research directions, this paper equips policymakers, practitioners, and academics with actionable insights to transform reconstruction into a catalyst for resilient, equitable, and sustainable development.